Rational screening of metal catalysts for selective oxidation of glycerol to glyceric acid from microkinetic analysis. Issue 2 (3rd September 2022) - Yan, Hao; Li, Shangfeng; Feng, Xiang; Lu, Jiarong; Zheng, Xiuhui; Li, Ruiying; Zhou, Xin; Chen, Xiaobo; Liu, Yibin; Chen, De; Shan, Honghong; Yang, Chaohe
Abstract: Rational screening of efficient supported metal catalysts is still a great challenge due to the complicated reaction mechanism for selective polyol oxidation. Exemplifying glycerol oxidation to glyceric acid as a model reaction, we perform a DFT assisted descriptor based microkinetic modeling to reveal the underlying mechanism. It is found that the addition/formation of OH − could polarize the metal surface (M‐OH*) to regulate the d ‐band center of Pt accompanied by the electron transfer from OH − to metal atoms, thus promoting the adsorption of glycerol. Moreover, the linear chemisorption energy and transition state energy scaling relations are well established on the formation energies of adsorbed C and O. Activity map obtained from descriptor based microkinetic analysis demonstrates that Pt and Ir metals exhibit the highest catalytic activity. Meanwhile, further analysis of the desorption energy and CC bond cleavage activation energy of glyceric acid product shows that Au and Pt metals display the optimal glyceric acid selectivity. Satisfactorily, these results from microkinetic analysis are in good agreement with the comparative experimental results. The insights revealed here may open a new avenue for rational design of transition metal catalysts in the bio‐polyol oxidation system.